Comparison of liquid and dried sodium citrate as the anticoagulant for Thrombotest and prothrombin time estimations. Issue 8 (August 1981) - Hoctor, D; Bottomley, J; Hyde, K; Gowenlock, A H; Maciver, J E
Abstract : Samples which are taken for the Quick one-stage prothrombin time estimation for the control of patients receiving oral anticoagulant treatment are by convention taken into liquid sodium citrate anticoagulant. Dried sodium citrate has been rejected on the grounds that excessive haemolysis causes activation of clotting factors and therefore falsely short clotting times. Tests were performed with both liquid and dried sodium citrate as an anticoagulant for prothrombin time and Thrombotest. No clinically significant difference between the values given by the two anticoagulants was observed.